THE EFFECT OF INTERNAL AUDITING IN COMBATING MONEY LAUNDERING - Dr. Azadeh Barati; Angham Awad Kanawi Al- Sawafi; Hajir Abdulameer Enayma Al- Farhan; SABAH SAADOON ABD ALI KATI AL SHGAEN; RASHA TALIB JABBAR FAHD AL_HAMD (Scholar Express Journals, 2022)
In this study, the phenomenon of money laundering was defined, and its effects were explained, in addition to mentioning this problem and the methods used to treat it, as this phenomenon has become one of the most important phenomena that trouble the countries of the world, due to its negative effects from the social, economic, political and administrative aspects of countries.Financial institutions, including banks, are still a major target of money launderers in order to transfer illegal funds to project funds, through weakness in the internal audit procedures applied in banks or through the lack of legal structure to combat this phenomenon in addition to other regulatory procedures.The internal audit has been defined and stated its most important objectives, as it aims to protect the institution’s assets and information from embezzlement and manipulation, as well as evaluating the performance of the multiple activities of the economic unit and indicating whether they are efficient or not, and one of its objectives is attention and prevention of fraud and errors and investigation to confront them in a timely manner.The most important internal audit standards are the criterion of independence, professional skill, and performance of the audit work. The requirements for the success of internal audit were also addressed, which were the numerical sufficiency and professional competence of internal audit staff, and stressed the impartiality in the work of the internal auditor and not to be biased towards the administration when practicing His work, as well as the internal audit procedures in combating money laundering and its role in limiting this phenomenon were mentioned.
Keywords: Money laundering; stages of money laundering operations; internal auditing